2005
DOI: 10.1161/01.res.0000158966.58380.37
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Early Action Potential Repolarization Causes Localized Failure of Sarcoplasmic Reticulum Ca 2+ Release

Abstract: Abstract-Depressed contractility of failing myocytes involves a decreased rate of rise of the Ca 2ϩ transient. Synchronization of Ca 2ϩ release from the junctional sarcoplasmic reticulum (SR) is responsible for the rapid rise of the normal Ca 2ϩ transient. This study examined the idea that spatially and temporally dyssynchronous SR Ca 2ϩ release slows the rise of the cytosolic Ca 2ϩ transient in failing feline myocytes. Left ventricular hypertrophy (LVH) with and without heart failure (HF) was induced in felin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
74
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 52 publications
11
74
0
Order By: Relevance
“…In addition, the detailed effects on Ca handling for each K current class differ somewhat. The reduction in I to can reduce the early AP repolarization (notch) and decrease the amount of I Ca during the early part of the AP because of a decreased electrochemical driving force (19,48). This can reduce the amount of SR Ca release, or at least reduce the synchronization of SR Ca release, which is important for synchronizing contraction.…”
Section: Potassium Current Alterations Influence Ca Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the detailed effects on Ca handling for each K current class differ somewhat. The reduction in I to can reduce the early AP repolarization (notch) and decrease the amount of I Ca during the early part of the AP because of a decreased electrochemical driving force (19,48). This can reduce the amount of SR Ca release, or at least reduce the synchronization of SR Ca release, which is important for synchronizing contraction.…”
Section: Potassium Current Alterations Influence Ca Handlingmentioning
confidence: 99%
“…Note that increases in transverse tubules would be required to prevent a reduction in surface-to-volume ratio in the much larger HF myocyte. Moreover, what looked like a spatial drop-out in ECC efficacy in feline HF myocytes (i.e., possibly missing transverse tubules) was shown to be attributed to the altered AP waveform with much less transient outward current (I to ) in HF (19). That is, without the early repolarization driven by I to , the early AP plateau is more positive and decreases the driving force for I Ca and thus limits junctional activation (48).…”
mentioning
confidence: 99%
“…They observed that when early repolarization is slowed, I Ca,L shows a decreased peak and slower kinetics, in spite of similar or greater total Ca 2+ influx compared to that with fast early repolarization. Slowdeveloping I Ca,L results in asynchronous SR Ca 2+ release, which is less efficient to rapidly increase [Ca 2+ ] i at systole (50,51). This alteration may become more accentuated, with progression to heart failure, when intrinsic reduction of I Ca,L amplitude may occur (51).…”
Section: How I To Can Affect Ca 2+ Homeostasismentioning
confidence: 99%
“…Slowdeveloping I Ca,L results in asynchronous SR Ca 2+ release, which is less efficient to rapidly increase [Ca 2+ ] i at systole (50,51). This alteration may become more accentuated, with progression to heart failure, when intrinsic reduction of I Ca,L amplitude may occur (51). One of the expected consequences would be slower and weaker contraction activation.…”
Section: How I To Can Affect Ca 2+ Homeostasismentioning
confidence: 99%
“…A major deficit in failing myocytes is the reduced Ca 2+ content of the SR, which is related to decreased expression and activity of the SR Ca 2+ -ATPase [84,92,146,153] and an increased Ca 2+ leak of the RyR2 due to hyperphosphorylation [84,94,112,122]. These defects, potentially aggravated by L-type Ca 2+ channel dysfunction [41,71,81,86,113,131,146,184] or t-tubular derangement [32,86,115,145,184] [17,81,113,115,146,184]. Decreased SR Ca 2+ -ATPase activity is partly compensated by increased expression and activity of the NCX [16,65,93,146,178,190] The underlying mechanisms for elevated [Na + ] i are incompletely understood, but may involve a decrease in Na + /K + -ATPase activity [58,156,169,172,175,206], enhanced Na + /H + -exchanger (NHE) activity [2,6,40,142], or an increase in a tetrodotoxin-sensitive persistent (late) I Na …”
mentioning
confidence: 99%